The Effect of Integrity and Effectiveness of Internal Control on Potential Accounting Fraud and Their Impact on Financial Accountability - Hanipa Kamil, Abi; Nurul Hidayah (Dinasti Publisher, 2022)
The public's doubts about several cases of abuse of authority by banking officials and employees have caused the public's trust to decrease in the banking sector, which should be a safe and reliable place to store funds for all Indonesian people. Public demands for accountability and transparency from the bank in disclosing the findings of fraud have forced banks to further improve their integrity and internal control. This study aims to examine the effect of integrity, effectiveness of internal control, on the potential for accounting fraud and its impact on financial accountability in Indonesian banks. This research uses Structural Ecuation Modeling (SEM) analysis. The population in this study is banking in Indonesia which is listed on the Indonesia Stock Exchange (IDX) in 2021, the total sample in this study is 54. The data are taken from questionnaires distributed to respondents. The results of this study indicate that the integrity and effectiveness of internal controls have a negative effect on the potential for accounting fraud, the integrity and effectiveness of internal controls have a positive effect on financial accountability, and the potential for accounting fraud has a negative effect on financial accountability.